Factors Influencing Outbreak of Diarrhoea among Children under the age of five years in Borno State - Lola N; Kever RT; Hamina D; Alhaji A (Ibom Medical Journal, 2025)
Introduction: Diarrhoea infection has been recognized as one of the world’s leading causes of morbidity and mortality, resulting in over two million deaths per year, especially children in resource-limited countries